FEASIBILITY OF EARLY Pinus taeda L. SELECTION TO ASSESS GROWTH VARIABLES IN PROGENY TEST - Flôres Júnior, Paulo César; Ishibashi, Vanessa; Monteiro de Matos, Jorge Luis; Tyszka Martinez, Diego; Rioyei Higa, Antonio (Floresta, 2021)
Forest species breeding programs require a long period-of-time for plants to reach the proper age to enable selecting superior genotypes, which is a critical factor in selection processes. Thus, the aims of the current study are to estimate genetic parameters in juvenile and adult plants (6, 10 and 20 years) in order to investigate genetic correlations between variables at different ages and at certain ages; as well as to determine whether it is possible performing efficient early selection in juvenile plants. The test was implemented in 1997; it comprised 120 progenies and followed a randomized block design, with five repetitions - linear plots comprised 5 plants at 2.5 m x 2.5 m spacing. DBH (cm), H (m) and VOL (m³) of all tested subjects were measured at the age of 6, 10 and 20 years. Variance components, genetic parameters, as well as genetic correlations between variables and between ages were estimated in Selegen REML/BLUP® software. Genetic parameter estimates have shown superiority at 10 years, in comparison to that estimated at 6 and 20 years. Variable ‘DBH’ has shown high genetic correlation to height (H) and volume (VOL), whereas DBH x VOL have shown high genetic correlation (0.98) in 10-year-old plants. With respect to genetic correlation between ages, 10-year-old plants have shown moderate correlation to 6- and 20-year-old plants. Early selection is indicated for 10-year-old plants, in 20-year cycles, since plants at this age have shown higher selection efficiency to predict gains in comparison to adult plants.